2016
DOI: 10.4067/s0718-95162016005000052
|View full text |Cite
|
Sign up to set email alerts
|

The physical properties, lignin distribution, chemical composition of fibers and gas exchange rate of kenaf (Hibiscus cannabinus L.) varieties under prolonged water deficiency

Abstract: The fundamental characteristics and physical properties of kenaf (Hibiscus cannabinus L.) fibers cultivated and subjected to three different water frequencies in Universiti Putra Malaysia, were analyzed. For deep analysis, which includes micro-scale viewing for identification of kenaf cell wall structure, fibers were viewed in order to study the physical characteristics, anatomy, and lignin distribution. The chemical composition was determined considering Technical Association of Pulp and Paper Industry (TAPPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The minimum values were observed in the morning in 2019 and in the evening in 2020, which are the hours when the arrival angles of the sun rays on the plants are more oblique. When the studies including seasonal measurements are examined, it is seen that the A values of the fully irrigated kenaf plant can reach up to 25-30 μmol CO 2 m -2 s -1 [11,12]. In parallel with the obtained values, [13] reported that the maximum net photosynthesis rate for Tainung 2 cv.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The minimum values were observed in the morning in 2019 and in the evening in 2020, which are the hours when the arrival angles of the sun rays on the plants are more oblique. When the studies including seasonal measurements are examined, it is seen that the A values of the fully irrigated kenaf plant can reach up to 25-30 μmol CO 2 m -2 s -1 [11,12]. In parallel with the obtained values, [13] reported that the maximum net photosynthesis rate for Tainung 2 cv.…”
Section: Resultsmentioning
confidence: 78%
“…The measurement time has been found to influence gs [39]. [12] stated that the values measured during the season in fully irrigated kenaf plants reached 0.95 mol H 2 O m -2 s -1 . [13] declared that the highest gs values reached during the day were 1.3 mol H 2 O m -2 s -1 and 1.75 mol H 2 O m -2 s -1 for Tainung 2 and Everglades 41 cultivars, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations